Accuracy of single-jet water meters during filling of the pipe network in intermittent water supply. Issue 10 (26th November 2017) - Walter, David; Mastaller, Miran; Klingel, Philipp
Abstract: In intermittently operated water distribution systems the air intruded into the pipe network through the filling and emptying process must inevitably exit the system at some point. Part of this air is discharged through service connections and thus through water meters. Due to this air flow, water meters are being used contrary to their actual conception. This article presents a study in which the measurement error of single-jet water meters due to the filling process of an empty service connection is experimentally examined. It shows that this error is caused mainly by the air flow before the water front reaches the water meter. The correlation between the measurement error and the air volume in front of the water meter is almost linear. The impact of the water front, the presence of water-air mixtures or unsteady flow processes however, is shown to have very little influence on the results.